The myth of the earth in the late lyric poetry of O. E. Mandelstam (Based on the material of the “First Voronezh Notebook”) - Minz, Bella A. (Известия Саратовского университета. Новая серия. Серия Филология: Журналистика, 2022)
Mandelstam’s creative thinking is similar to the mythological one. This is refl ected in his lyric poetry as an artistic whole and in individual author’s myths. The article presents the analysis of some features of the author’s myth about the earth, which was formed in the “First Voronezh Notebook” by O. Mandelstam. The following tasks are set: to identify the features of the poetics of the mythological type in the complex of elements associated with the image of the earth; to show their semantic and fi gurative unity, as well as their role in the poetic attitude of Mandelstam in later years. The analysis is carried out mainly at the level of the fi gurative-motivic structure. The article also refl ects intertextual connections, special features of the lyrical plot, artistic space and other elements of poetics. Combinations of elements, their modifi cations, intertextual connections, including those within cyclic structures, are taken into account. The analysis has shown that the author’s myth about the earth is one of the foundations of the poet’s worldview in the “First Voronezh Notebook” and is closely related to both his ideas about the Word, poetry, the poet’s fate, and his understanding of the roots of national existence in their relation to the modern era. The myth of the earth largely determines the originality of the artistic space and optics of the poems of the “First Voronezh Notebook”. Having considered this phenomenon, the author of the article was able to clarify the idea of the most controversial points of the ideological position of Mandelstam in his later years.